Constraints and potentials for implementing the green building rating tool for government buildings in Malaysia / Azlina Abdul Hamid and Mohamed Rashid Embi - Abdul Hamid, Azlina; Embi, Mohamed Rashid (2012)
The green building movement is growing rapidly across the world. In Malaysia, there are a few government buildings built to promote the practice of energy efficiency designs; for example Low Energy Building by The Energy, Water and Communication Ministry (KeTTHA). However, this building was not classified or rated as a green building design because it does not acquire any certification of green building index. This paper will discuss the necessity for government buildings to obtain certificates of green building rating tool. A survey was carried out on some of the building industries’ representatives such as Government building implementers, architects, engineers, educators, contractors and federal government agencies. Based on the survey, this paper has pointed out the constraints and potentials for implementing the green building rating tool for government buildings in Malaysia.